2016
DOI: 10.1016/j.jcm.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Lumbar Fusion Surgery With Relevance to Chiropractic Practice

Abstract: This article describes the indications for fusion, common surgical practice, potential complications, and relevant published chiropractic literature. This review includes 10 cases that showed positive benefits from chiropractic manipulation, flexion-distraction, and/or manipulation under anesthesia for postfusion lumbar pain. Chiropractic care may have a role in helping patients in pain who have undergone lumbar fusion surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…To date there are no published systematic reviews that evaluate chiropractic or spinal manipulation after lumbar fusion [28]. A systematic review of physical therapy and rehabilitation treatments identified good evidence to recommend patient education as a part of pre-and postoperative fusion rehabilitation, moderate evidence to recommend neutral spine control exercise to increase core strengthening as part of operative fusion rehabilitation, and moderate evidence for adding postoperative psychological coping techniques to a rehabilitation program [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there are no published systematic reviews that evaluate chiropractic or spinal manipulation after lumbar fusion [28]. A systematic review of physical therapy and rehabilitation treatments identified good evidence to recommend patient education as a part of pre-and postoperative fusion rehabilitation, moderate evidence to recommend neutral spine control exercise to increase core strengthening as part of operative fusion rehabilitation, and moderate evidence for adding postoperative psychological coping techniques to a rehabilitation program [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports describe clinical improvements with chiropractic care in patients with postsurgical lumbar spine pain [21][22][23][24][25][26][27]. There are no cohort studies or experimental designs reporting on the outcomes of care provided by chiropractors in patients with prior lumbar fusion [28]. A recent VA research agenda from a stateof-the-art research conference on non-pharmacological care of chronic musculoskeletal conditions identified postoperative spine pain as a research priority for manual therapies, including manipulation and massage [29].…”
Section: Introductionmentioning
confidence: 99%
“…There was a large body of lower-level studies that were not assessed for quality. This included 1 scoping review [31], 1 narrative review [32], 14 case series [33][34][35][36][37][38][39][40][41][42][43][44][45][46], 23 case reports , and 2 commentaries [70,71]. Ten of the case reports described 53 cases following discectomy, 16 reports described MMT in 143 cases post-laminectomy, 16 reports described MMT care for 67 cases after fusion, 1 report discussed post-surgical treatment in 8 cases after artificial disc replacement, and 1 report discussed care in 3 cases following implantation of spinal cord stimulators.…”
Section: Literature Reviews Case Reports and Commentariesmentioning
confidence: 99%
“…It has been estimated that as much as 20% to 36% of all cases of failed back surgery may be due to epidural fibrosis [ 22 ]. Nevertheless, for post-fusion lumbar pain there is limited evidence for the safety and efficacy of chiropractic treatment and no guidelines to aid with therapeutic decision-making [ 23 ].…”
Section: The Principle Of Spinal Adhesionsmentioning
confidence: 99%